Characterisation of teacher professional knowledge and skill through content representations from tertiary chemistry educators. Issue 2 (21st February 2018) - Schultz, M.; Lawrie, G. A.; Bailey, C. H.; Dargaville, B. L.
Abstract : An established tool for collating secondary teachers' pedagogical content knowledge (Loughran's CoRe) has been adapted for use by tertiary educators. Chemistry lecturers with a range of levels of experience were invited to participate in workshops through which the tool was piloted, refined and applied. We now present this refined tool for the tertiary teaching community to consider adopting. The teaching approaches of over 80 workshop participants were collected using the tool in a broad survey of tertiary chemistry teaching strategies. Participation in the workshops led to a significant gain in personal PCK for some individuals. Analysis of responses received in the workshops revealed that the consensus model of secondary teacher professional knowledge and skill is also applicable to the tertiary level, and that the CoRe is a useful way to gain insight into the knowledge bases and topic-specific professional knowledge of tertiary chemistry teachers. The data were aggregated and coded inductively to distil the types of strategies commonly found to be useful for teaching particular tertiary chemistry topics. This resulted in collation of over 300 teaching strategies for 19 different chemistry topics, representing significant topic-specific professional knowledge of tertiary practitioners. To share and sustain this collection of teaching strategies, a website was built that is searchable by either chemistry topic or by type of teaching strategy, making it immediately useful to practitioners. Usage analytics data for the website confirm that many users have accessed the resource, showing that this is a practical way to transfer information between chemistry educators.